Ginseng and health outcomes: an umbrella review - Li, Zhongyu; Wang, Yang; Xu, Qing; Ma, Jinxin; Li, Xuan; Tian, Yibing; Wen, Yandong; Chen, Ting (Frontiers in Pharmacology, 2023)
Background: Despite the large number of meta-analytic studies on ginseng conducted to date, a comprehensive summary of the evidence and methodological quality of ginseng-related research remains lacking. Methods: PubMed, Embase, the Cochrane Library of Systematic Reviews, and Scopus were searched for meta-analyses assessing the efficacy and safety of ginseng from inception to July 31, 2022. The Assessment of Multiple Systematic Reviews-2 (AMSTAR-2) and Grading of Recommendations Assessment, Development and Evaluation (GRADE) systems were used to assess the methodological quality and level of evidence for each meta-analysis, and the results were summarized in narrative form. Results: Nineteen eligible meta-analyses were identified from among 1,131 papers. When compared with control treatments (mainly placebo), ginseng was beneficial for fatigue and physical function, sexual function, menopausal symptoms, metabolic indicators, inflammatory markers, unstable angina as well as respiratory disease. Common adverse effects of ginseng consumption included gastrointestinal symptoms and potential bleeding, but no serious adverse reactions were reported. Conclusion: Although the available evidence suggests that ginseng can aid in improving a wide range of clinical outcomes, improvements in the methodological quality of published meta-analyses are required. In addition, the clinical effects of ginseng must be further confirmed in high-quality randomized trials.